HUBUNGAN PRE EKLAMSI BERAT DENGAN TERJADINYA IUGR PADA JANIN - Roudatul Hikmah (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2017)
Intra-Uterine Grout Retardation (IUGR) is the abnormal growth of the fetus in uterine developmental disturbances or disorders. This study aims to determine the level of incidence of IUGR on mothers with PEB (severe Pre-eclampsia) in Abdoer Rahem Situbondo hospitals. The research design in this study was used